2016
DOI: 10.1371/journal.pone.0156604
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic mRNA Expression of FAS, FASL, and FOXP3 Genes Is Associated with the Pathophysiology of Chronic HCV Infection

Abstract: This study aimed to evaluate the relative mRNA expression of Fas receptor (FAS), Fas ligand (FASL), and forkhead box protein 3 (FOXP3) in liver biopsy specimens obtained from patients with viral and non-viral chronic hepatitis and correlate their expression with the fibrosis stage. A total of 51 liver biopsy specimens obtained from HBV (n = 6), HCV (n = 28), and non-viral hepatic disease (NVHD) (n = 9) patients and from individuals with normal liver histology (n = 8) (control—CT) were analyzed. Quantifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…As Th17-derived IL-6 and IL-21 could block the differentiation of Tregs [ 47 ], we propose that increased expressions of IL-21 mRNA by IL-23 agonist could might have caused a corresponding reduction in the FoxP3 mRNA expressions. Importantly, our data on the mRNA expressions of IL-17A, IL-22, STAT1, SOCS3, MxA, and FoxP3 in the PBMCs are consistent with the changes of these cytokines in livers reported in other studies [ 48 , 49 , 50 , 51 , 52 ]. Our data also suggest that the imbalance of T-cell subsets distribution might have important influences on disease progression and clinical outcome.…”
Section: Discussionsupporting
confidence: 92%
“…As Th17-derived IL-6 and IL-21 could block the differentiation of Tregs [ 47 ], we propose that increased expressions of IL-21 mRNA by IL-23 agonist could might have caused a corresponding reduction in the FoxP3 mRNA expressions. Importantly, our data on the mRNA expressions of IL-17A, IL-22, STAT1, SOCS3, MxA, and FoxP3 in the PBMCs are consistent with the changes of these cytokines in livers reported in other studies [ 48 , 49 , 50 , 51 , 52 ]. Our data also suggest that the imbalance of T-cell subsets distribution might have important influences on disease progression and clinical outcome.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, certain Treg subsets stimulate fibrosis through the release of TGFβ. Recent studies have shown increased number of regulatory T cells in peripheral blood and in liver tissue of chronic HCV patients [28, 29]. Similarly, we found significantly higher number of Tregs in peripheral blood of all groups of patients in comparison to control, indicating strong suppression of immune response.…”
Section: Discussionsupporting
confidence: 80%
“…The literature also provides data that correlate FOXP3 expression and the presence of Treg cells with higher levels of inflammatory activity and the degree of liver fibrosis in chronic viral hepatic diseases ( 74 76 ). Thus, in patients with chronic hepatitis C infection, the − 3279C > A polymorphism may mediate Treg activation in more advanced stages of liver inflammation and fibrosis, as shown by the relationships established in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in the absence of Th2-specific signaling, FOXP3+ Treg cells can express high levels of IFN-γ and T-bet, which are Th1-specific transcription factors, making them susceptible to conversion to the Th1 profile ( 79 , 80 ). Reportedly, blockage of the Treg-Th2 conversion generated by the * G allele of the − 924A > G polymorphism ( 76 ) can promote an immune balance favorable to the development of a Th1 profile, which is considered crucial for the control of viral replication by tissue inflammation ( 81 , 82 ). This situation would lead to tissue damage, with a subsequent increase in liver enzyme levels in the blood of these patients.…”
Section: Discussionmentioning
confidence: 99%